An interlocking approach for the rebar-to-concrete contact in bond. Issue 8 (4th April 2021) - Tirassa, Max; Fernández Ruiz, Miguel; Muttoni, Aurelio
Abstract : The bond response of deformed bars in structural concrete is a phenomenon governed, to a large extent, by the rib-to-concrete contact and interaction, with contact forces depending on both material properties and the kinematics between the contact surfaces (slip and potential separation between the bar and concrete). This phenomenon, presenting similarities with aggregate interlocking in cracked concrete, is difficult to investigate in an experimental manner by means of conventional test arrangements. In this work, an experimental and theoretical investigation on the phenomenon was conducted by means of an innovative experimental test setup performed with bar off-cuts and allowing tracking of the development of bond and confinement stresses for given contact kinematics. The surface of the rebars was scanned to analyse the contact and roughness properties for various cases. The experimental results were analysed using a mechanical model accounting for the surface properties and rib-to-concrete mechanical engagement. Good agreement in terms of the maximum stresses and load–displacement curves was obtained. On that basis, the practical implications of calculating bond stresses on cracked concrete are discussed.